TINGKAT KEADILAN DISTRIBUTIF DAN KEADILAN INTERAKSIONAL KOMPENSASI TERHADAP KEPUASAN KERJA PADA RUMAH SAKIT PKU MUHAMMADIYAH BIMA - Jaenab Jaenab; Ety Kurniawati (Master of Management, Mataram University, 2020)
This study aims to determine and analyze the influence of distributive justice and interactional justice compensation on employee job satisfaction at PKU Muhammadiyah Hospital in Bima. This type of research is associative using a quantitative approach while all variables are measured using a Likert scale. The number of samples as respondents used was 120 people. Testing instruments using the validity and reliability test. To analyze the data using multiple regression analysis with SPSS version 20, t-test, f test, and adjusted coefficient determination (R) test. From the regression results for this study the equation is obtained, namely Y = 23.411 + - 014X1 + 0.750X2. R-value (Correlation Coefficient) obtained is 0.688 and R Squier value (Coefficient of determination) is 0.473 or 47%. The results of this study indicate that partially distributive justice does not have a positive and significant effect on employee job satisfaction, interactional justice compensation has a positive and significant effect on employee job satisfaction. Together distributive justice and compensatory interactional justice have positive and significant effects on employee job satisfaction.